Advanced Biosensing Technologies: Leading Innovations in Alzheimer’s Disease Diagnosis - Stephen Rathinaraj Benjamin; Fábio de Lima; Paulo Iury Gomes Nunes; Rosa Fireman Dutra; Geanne Matos de Andrade; Reinaldo B. Oriá (Chemosensors)
Diagnosing Alzheimer’s disease (AD) remains a significant challenge due to its multifactorial nature and the limitations of traditional diagnostic methods, such as clinical assessments and neuroimaging, which often lack the specificity and sensitivity required for early detection. The urgent need for innovative diagnostic tools is further underscored by the potential of early intervention to improve treatment outcomes and slow disease progression. Recent advancements in biosensing technologies offer promising solutions for precise and non-invasive AD detection. Electrochemical and optical biosensors, in particular, provide high sensitivity, specificity, and real-time detection capabilities, making them valuable for identifying key biomarkers, including amyloid-β (Aβ) peptides and tau proteins. Additionally, integrating these biosensors with nanomaterials enhances their performance, stability, and detection limits, enabling improved diagnostic accuracy. Beyond nanomaterial-based sensors, emerging innovations in microfluidics, surface plasmon resonance (SPR), and artificial intelligence-assisted biosensing further contribute to the development of next-generation AD diagnostics. This review provides a comprehensive analysis of the latest advancements in biosensing technologies for AD, highlighting their mechanisms, advantages, and future perspectives in detecting biomarkers from biological fluids.